2022
DOI: 10.6018/eglobal.504291
|View full text |Cite
|
Sign up to set email alerts
|

Resultados de distracción para el cuidado en oncología pediátrica desde la evidencia de enfermería: revisión integrativa

Abstract: Introduction: Pediatric cancer causes a radical change in the external and internal environment of the child or adolescent affecting their development and growth. Objective: To synthesize the findings of nursing studies that published results in physical, psychological, social and immune health through the use of distraction strategies for care. Methodology: Integrative literature review, qualitative descriptive and retrospective based on parameters established by Whittemore and Knafl with five stages. Inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the other hand, several studies also indicated the use of music therapy and hypnosis have shown a beneficial effect for the treatment of pain. Regarding the pediatric oncology population (Avila et al, 2022) & their collaborators (2022) mention that alternative therapies such as music therapy, therapeutic massage and physical activity promote adaptation and distraction in the hospital setting, where they obtained beneficial results in physical, psychological, social and immune health. (Hidalgo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies also indicated the use of music therapy and hypnosis have shown a beneficial effect for the treatment of pain. Regarding the pediatric oncology population (Avila et al, 2022) & their collaborators (2022) mention that alternative therapies such as music therapy, therapeutic massage and physical activity promote adaptation and distraction in the hospital setting, where they obtained beneficial results in physical, psychological, social and immune health. (Hidalgo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%